INVESTIGATING THE RELATIONSHIP BETWEEN RADIOLOGICAL TECHNOLOGISTS' WORKLOAD AND JOB SATISFACTION IN SAUDI ARABIAN HEALTHCARE FACILITIES - Abdullah Hassan Ahmed Qahl, Norah Abdullah Aldakhil, Sultan Awadh Alyabsi, Thamer Suleiman Bin Rumah, Waleed Mohammed Almutairi, Abdulrahman Abdullah Alsadrani, (Chelonian Research Foundation, 2022)
Radiological technologists play a crucial role in the healthcare system, conducting various diagnostic imaging examinations and ensuring patient safety. However, the increasing demand for imaging services has led to higher workloads, which may impact job satisfaction. This study aimed to investigate the relationship between radiological technologists' workload and job satisfaction in Saudi Arabian healthcare facilities. A cross-sectional survey was conducted among 450 radiological technologists working in public and private hospitals across the country. Workload was assessed using the NASA Task Load Index (NASA-TLX), while job satisfaction was measured using the Job Satisfaction Survey (JSS). The findings revealed a significant negative correlation between workload and job satisfaction (r = -0.68, p < 0.001). Multiple linear regression analysis showed that workload, along with years of experience and professional development opportunities, were significant predictors of job satisfaction (R² = 0.52, F(3, 446) = 158.43, p < 0.001). The study highlights the need for healthcare organizations to implement strategies to manage workload effectively and promote job satisfaction among radiological technologists, ultimately enhancing patient care quality and staff retention. Keywords: radiological technologists, workload, job satisfaction, healthcare facilities, Saudi Arabia